Evaluasi Bidang Penataan Bangunan Gedung Dinas Pekerjaan Umum dan Tata Ruang Kabupaten Sumenep - Fitriaji, Nurul; Megawati, Suci (Publika, 2024)
The Sumenep District Public Works and Spatial Planning Office is one of the offices formed due to the merger of regional apparatus organizations. The Building Arrangement Division is one of the fields in the office that was formed as a result of the merger. The merger can be a challenge for the Building Arrangement Division in carrying out its duties. The Building Arrangement Division has an activity program in the form of organizing building buildings in the Regency / City area, granting building permits and building function certificates. This research evaluates the Building Structuring Division of the Sumenep District Public Works and Spatial Planning Office, especially in 2022. The research method used is using descriptive research type, and using a qualitative approach. The focus of this research is using evaluation criteria consisting of effectiveness, efficiency, adequacy, equity, responsiveness and accuracy. The data collection technique is using interviews, observation, documentation, with data analysis techniques in the form of data collection, data reduction, data presentation, and conclusion drawing. The results showed that the program activities of the Building Structuring Division in 2022, on the criteria of effectiveness, adequacy, responsiveness, and accuracy were well implemented. However, the criteria of equity and efficiency, especially information equity and time efficiency, are still not well implemented. Where, due to the lack of information / socialization from the Building Structuring Division about building permits and certificates of fitness for function, and the slow response of applicants in making building permits or certificates of fitness for function, the achievement of the target performance indicators of the Building Structuring Division is less than the desired target